Sleep in Drosophila - Greenspan, Ralph (Henry Stewart Talks, 2008)
Evolution of sleep, Sleep-like behavior in Drosophila, Physiological and pharmacological characteristics, Genetics of sleep: neurotransmitter and signal transduction systems
Reviewed at 2018/06/01